Development of probiotic‐based immunoparticles for pulmonary immunization against Hepatitis B. (16th July 2014) - Sharma, Kulbhushan; Malik, Basant; Goyal, Amit K.; Rath, Goutam
Abstract Objectives The present study was oriented towards the development of pulmonary vaccine for Hepatitis B using probiotic biomass as an adjuvant. Methods The antigen was spray dried in presence of heat treated, formalin treated and live probiotic biomass. Key findings The results indicated that the biomass itself without any additional cryoprotectant is capable of protecting the structural integrity of the antigen. We were able to retain more than 80% of the antigenicity. The scanning electron microscopic images indicated that the formulation bearing live probiotic biomass have spherical size, while the formulations with heat and formalin treated biomass shows irregular shaped particles. The developed formulations were further evaluated for in‐vivo immune response. Immunoglobulin G (IgG) titre results were found to be comparable with marketed (aluminium adsorbed) formulations while significantly higher secretory immunoglobulin A titre showed better mucosal immune response than marketed formulation. Conclusion Therefore, the probiotic biomass can be utilized as a potential cryoprotectant as well as a potent immunomodulator.